Chapter Politica e politiche dell'Italia in Africa, 2008-2018 - MORONI, SHEYLA (Studi e saggi, 2021)
The contribution looks at the Italian policies towards Africa in order to attest if and how migration issues influenced the political agenda and the decision-making process both of the government and the parliament, respectively, between 2008 and 2018. This period witnessed the development of an alleged new course for Italian policies vis-à-vis Africa and some African countries in particular. Here we focus on Nigeria and Senegal. An outline of the official visits made by Italian politicians to Africa and the scrutiny of parliamentary debates on African issues allows to assess the divide between the rhetoric of a supposed 'new course', with Italy at the forefront of a new Euro-Africa partnership, and the continuity of 'old' concerns on matters such as the control of flows and mobility.